The Relationship of Characteristics of Hypertensive Patients to the Level of Adherence to Taking Hypertension Medication at the Pal Tiga Health Center, Pontianak - Zakiah, Mistika; Saputra, Restu; Redha, Muhammad; Deni, Muhammad; Ansharullah, Ansharullah (Jurnal Indonesia Sosial Sains, 2024)
Background: One of the non-communicable diseases that is a serious health problem today is hypertension. It is often referred to as the silent killer because sufferers usually do not know they have hypertension before checking their blood pressure. Objective: To determine the relationship between patient characteristics (education, level of knowledge, and BPJS safety) and the level of adherence to hypertension medication at the Pal Tiga Pontianak Health Center. Method: This research uses a cross-sectional method. The sample in this study was 89 hypertension patients at the Pal Tiga Pontianak Health Center. The research instrument used in this study was in the form of a questionnaire filled out by the respondents. The questionnaires used were the Morisky Medication Adherence Scale (MMAS-8) and the Hypertension Knowledge-Level Scale (HK-LS). The correlation test used is a Spearman test. Result: the relationship between education, knowledge level, and BPJS participation on the level of adherence to hypertension medication of respondents, respectively p-value was obtained of 0.879; 0.189; and 0.802. Conclusion: There is no relationship between education, knowledge level, and BPJS participation in compliance with taking hypertension medication at the Pal Tiga Pontianak Health Center. this is done by interviewing patients with an MMSA compliance questionnaire abstract that does not need to be divided into.